Treating an Epidemic During a Pandemic: Experience Treating Opioid Use Disorder at the Baltimore Convention Center Field Hospital. (21st October 2022) - Chamberlain, Catherine J.; Siddiqui, Zishan K.; Chaudhary, Mihir J.; Kantsiper, Melinda E.
Abstract: During the COVID-19 pandemic, access to addiction treatment has plummeted. At the same time, patients with opioid use disorder are at higher risk of COVID-19 infection and experience worse outcomes. The Baltimore Convention Center Field Hospital (BCCFH), a state-run COVID-19 disaster hospital operated by Johns Hopkins Medicine and the University of Maryland Medical System, continues to operate 14 months into the pandemic to serve as an overflow unit for the state's hospitals. BCCFH staff observed the demand for opioid use disorder care and developed admission criteria, a pharmacy formulary, and case management procedures to meet this need. This article describes generalized lessons from the BCCFH experience treating substance use disorder during a pandemic.